Economic cooperation organzation anti drug activities and lack of law harmonization / Mohammad Naji Shah Mohammadi ... [et al.] - Mohammadi, Mohammad Naji Shah; Mat Basir, Salawati; Moghadamfard, Mohammad; Farmani, Yaser; Sobatian, Elmira (2014)
In order to combat drug trafficking, regional cooperation among countries seems inevitable. In addition to cooperation in the area of drugs control, there is a pressing need for the institutionalization of a regional framework for law enforcement cooperation to deal with issues related to transnational crime. Such cooperation must be organized in the form of an effective mechanism based on specified international and regional agreements and those identified by individual Member States. Drug trafficking in ECO poses serious threats to public health, security and economy of the region. Consequently, the issue has gained immense importance within the Organization‟s framework of activities. As the production and use of illicit drugs continue to imperil the region‟s socio-economic progress, the ECO Member States have taken steps to strengthen their respective national drug control systems. By having brief look at ECO member‟s anti-drug law, it can be seen that there is difference between ECO member anti-drugs law and their criminal justice system. Despite all ECO members ratified international drug convention such as 1988 drug convention - which try to make coordinated approach to fight with drug trafficking - ECO still there is some gaps between ECO members drug policy and need for harmonized system is clearly egregious. This paper seeks to point out Lack of harmonization in the Eco Area with a Critical Analysis method and finally come up with some suggestions on the issue. Maximum of 250 words. (Century Gothic, font 9)